X-ray CT Analysis of FNS Mortars Mixed with Converter Slag Fine Aggregate (Global Journal of Science Frontier Research, 2021)
Abstract not found
Keywords: ferronickel slag (FNS); converter slag (BOF); X-ray CT analysis; supplementary cementitious materials (SCMs)